A two‐decade population‐based study on the effect of hypertension in the general population with obesity in the United States. Issue 3 (7th February 2023) - Kong, Gwyneth; Chin, Yip H.; Lim, Jieyu; Ng, Cheng H.; Kannan, Shankar; Chong, Bryan; Lin, Chaoxing; Chan, Kai E.; Anand, Vickram V.; Lee, Ethan C. Z.; Loong, Shaun; Wong, Zhen Y.; et al.
Abstract: Objective: With rising prevalence of hypertension and obesity, the effect of hypertension in obesity remains an important global issue. The prognosis of the US general population with obesity based on hypertension control was examined. Methods: This study examined participants from the National Health and Nutrition Examination Survey between 1999 and 2018. Individuals with obesity were stratified into no hypertension, controlled hypertension, and uncontrolled hypertension. The study outcome was all‐cause mortality. Cox regression of all‐cause mortality was adjusted for age, sex, ethnicity, diabetes, and previous myocardial infarction. Results: Of 16, 386 individuals with obesity, 53.1% had no hypertension, 24.7% had controlled hypertension, and 22.2% had uncontrolled hypertension. All‐cause mortality was significantly higher in uncontrolled hypertension (17.1%), followed by controlled hypertension (14.8%) and no hypertension (4.0%). Uncontrolled hypertension had the highest mortality risk (hazard ratio [HR] 1.34, 95% CI: 1.13‐1.59, p  = 0.001), followed by controlled hypertension (HR 1.21, 95% CI: 1.10‐1.34, p  < 0.001), compared with no hypertension after adjustment. The excess mortality trend was more pronounced in females, those with diabetes, and those older than age 65 years. Conclusions: The incremental mortality risk in controlled and uncontrolled hypertension, compared with the normotensive counterparts, irrespective of sex, age, and diabetes status, urges health care providers to optimize hypertension control and advocate weight loss to achieve better outcomes in obesity.